The influence of lentivirus-mediated CXCR4 RNA interference on hepatic metastasis of colorectal cancer - WANG, TIAN-BAO (D.A. Spandidos, 2014)
The aim of this study was to construct a lentiviral vector of CXCR4-siRNA (Lenti-CXCR4-siRNA) and investigate whether the vector can inhibit the growth, migration, invasion and hepatic metastasis of colorectal cancer (CRC). RT-PCR and western blotting were employed to identify the ideal RNA interference sequence. Lenti-CXCR4-siRNA was constructed and transfected into the SW480 cell line. We used RT-PCR and western blotting to measure the expression of CXCR4 RNA and protein, respectively; the MTS assay to assess the proliferation of SW480 cells; transwell chambers to estimate the inhibitory effect on migration and invasion; and the Balb/c nude mouse model of CRC to examine the inhibition of hepatic metastasis. The relative expression of the CXCR4 gene and protein was 5.4 and 18.95%, respectively, in the siCXCR4 group. The genes in the expression plasmid pLenti-CXCR4-siRNA were in the correct order. In the SW480, nonsense control (NC) and the Lenti-CXCR4-siRNA groups CXCR4 RNA levels were, respectively, 0.54±0.06, 1.00±0.03 and 0.11±0.04 (P=0.0001); CXCR4 protein levels were 0.60±0.03, 0.72±0.03 and 0.18±0.02 (P=0.0001); the OD value was 1.38±0.04 (P=0.0050), 1.28±0.05 (P=0.0256) and 0.92±0.06; SW480 cell number in migration test was 32±6.85, 32.63±1.69 and 0.75±0.71 (P=0.0000); SW480 cell number in the invasion test was 29.13±10.3, 30.38±6.09 and 0.63±0.74 (P=0.0000); hepatic metastasis number was 7.10±3.98 (P=0.034), 7.50±4.09 (P=0.019) and (3.50±2.51); hepatic metastasis mean weight (in g) was 2.25±2.51 (P=0.000), 2.11±2.38 (P=0.000) and 1.45±2.07. Lenti-CXCR4-siRNA constructs were correctly constructed and effectively inhibit the expression of CXCR4 RNA and protein, reducing the proliferation, migration, invasion capacity of SW480 cells and hepatic metastasis of CRC.